Retomando a consciência: reações conservadoras a partir do debate sobre família e gênero - Freire, Laura (2018)
The present dissertation exposes the political performance of a group of religious conservatives in the public sphere. Therefore, it articulates two distinct empirical fields: the debates and voting of the Municipal Plan of Education (PME) in Toledo-Paraná, and the meetings for studies of the Order. The main objective is to understand the cosmology of this group, its performance in the public sphere and the meanings and circulation of the categories debated by them. The PME voting process is treated as an event, a paradigmatic episode that provoked a reaction from which the Conservative Christian Association was institutionalized, seeking to legitimize in the public space a social representation of family and gender based on a divine-natural conception. Through bibliographic analysis, especially the anthropological debates about feminism and poststructuralism, fieldwork with interviews and direct observation in meetings of the Order and the data collection of specific documentation produced and available by them, I try to show how the conservative cosmology of this group is established and how the actions of these agents impact on social reality by limiting the advance of democracy.